Chloroplast‐localized BICAT proteins shape stromal calcium signals and are required for efficient photosynthesis. Issue 2 (31st August 2018) - Frank, Julia; Happeck, Ricardo; Meier, Bastian; Hoang, Minh Thi Thanh; Stribny, Jiri; Hause, Gerd; Ding, Haidong; Morsomme, Pierre; Baginsky, Sacha; Peiter, Edgar
Summary: The photosynthetic machinery of plants must be regulated to maximize the efficiency of light reactions and CO2 fixation. Changes in free Ca 2+ in the stroma of chloroplasts have been observed at the transition between light and darkness, and also in response to stress stimuli. Such Ca 2+ dynamics have been proposed to regulate photosynthetic capacity. However, the molecular mechanisms of Ca 2+ fluxes in the chloroplasts have been unknown. By employing a Ca 2+ reporter‐based approach, we identified two chloroplast‐localized Ca 2+ transporters in Arabidopsis thaliana, BICAT1 and BICAT2, that determine the amplitude of the darkness‐induced Ca 2+ signal in the chloroplast stroma. BICAT2 mediated Ca 2+ uptake across the chloroplast envelope, and its knockout mutation strongly dampened the dark‐induced [Ca 2+ ]stroma signal. Conversely, this Ca 2+ transient was increased in knockout mutants of BICAT1, which transports Ca 2+ into the thylakoid lumen. Knockout mutation of BICAT2 caused severe defects in chloroplast morphology, pigmentation and photosynthetic light reactions, rendering bicat2 mutants barely viable under autotrophic growth conditions, while bicat1 mutants were less affected. These results show that BICAT transporters play a role in chloroplast Ca 2+ homeostasis. They are also involved in the regulation of photosynthesis and plant productivity. Further work will be required to reveal whether the effect on photosynthesis is a direct result of their role as Ca 2+ transporters.